PENGARUH PENGGUNAAN DOLLAR SINGAPURA DI KAWASAN WISATA LAGOI TERHADAP PEREKONOMIAN DOMESTIK BINTAN 2010-2013 - YUSAZ, DEVI NATASYA; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about the influence of the use of Singapore Dollar in Lagoi tourist area toward Bintan domestic economy in 2010-2013. Bintan District is one of the region that established as Free Trade Zone which gives chance to Singapore to invest mainly in tourism sector through PT. Bintan Resort Cakrawala (BRC). This investment is directly impacted with particular matter such as the use of foreign currency, that is Singapore Dollar. This matter gives influence to the enhancement of Bintan domesctic economy. The writer collects data from journals, books, essay, legislations, reports and online media to analyze the influence of Singapore dollar toward Bintan domestic economy. The theoretical framework applied in this research are neoliberalism perspective, the theory of international investment and foreign exchange concept. The research shows that the using of Singapore dollar in Lagoi tourist is considerably influential to Bintan economy domestic enhancement which produced by tax collection that accumulated to Local Own-source Revenue (PAD). The economy enhancement also gives impact to Regional Gross Domestic Product (PDRB) and Bintan district economic growth. Â  Key words: Tourism, Investment, Political-Economy, Singapore Dollar, Economic growth.